Interactive Animation-Based Learning Media Using Plotagon Studio for a Digital Transformation Course - Day Ramadhani Amir; Fatmila Sofiyatus Zahroh; Regita Cahyani (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2026)
The rapid advancement of digital technology has significantly transformed educational practices, requiring lecturers to develop innovative, interactive, and technology-integrated learning media that can enhance student engagement and improve learning effectiveness. In higher education contexts, digital learning media plays an essential role in creating meaningful learning experiences by facilitating knowledge delivery through more accessible, engaging, and learner-centered approaches. One of the emerging technologies with potential applications in education is Plotagon Studio, a 3D character-based animation application that enables educators to present learning materials through visual storytelling, animated representations, and interactive communication. This study aims to examine the utilization of Plotagon Studio as an interactive animation-based learning medium in the Digital Transformation course. This research employed a descriptive qualitative approach through a literature review to analyze the pedagogical potential and effectiveness of animation-based learning media in supporting digital learning processes. The findings reveal that the integration of Plotagon Studio contributes to improving students’ learning motivation, conceptual understanding, creativity, communication skills, and digital literacy competencies. Furthermore, the implementation of interactive animation media supports the principles of 21st-century learning by promoting student-centered learning environments, active participation, critical thinking, and technological competence development. Therefore, Plotagon Studio represents a promising and effective digital learning medium that can support instructional innovation and enhance the quality of learning experiences in the Digital Transformation course.